Preoperative malnutrition is a risk factor for prolonged postoperative ileus for patients undergoing gastrointestinal surgery - Zhu, Zhenming; He, Baoguo; He, Juan; Ma, Xuan; Gao, Qun; Huang, Yinghui; Chu, Yuning; Ma, Li (Frontiers in Nutrition, 2025)
BackgroundProlonged postoperative ileus (PPOI), a common complication after gastrointestinal (GI) surgery, seriously affects the postoperative recovery rate. However, there are few previous studies on the effect of preoperative nutritional status on the occurrence of PPOI in patients with GI cancer.ObjectiveTo evaluate the value of preoperative nutritional status for predicting the occurrence of PPOI in patients undergoing GI surgery.MethodsWe retrospectively analyzed the clinical data of GI cancer patients who were admitted to our hospital between June 2021 and June 2023. The nutritional status of all patients was assessed using the Nutritional Risk Screening 2002 (NRS2002) and the Patient-Generated Subjective Global Assessment (PG-SGA). The independent risk factors for PPOI identified via univariate and multivariate logistic regression analyses were used to establish nomogram for the prediction of PPOI.ResultsThe clinical data of 310 patients with GI cancer who underwent surgical resection were analyzed. PG-SGA score, serum albumin concentration, hemoglobin concentration, operation time, tumor stage, and previous abdominal surgery are independent risk factors for PPOI. The nomogram developed to predict PPOI performed well [area under the curve (AUC) = 0.835]. The calibration curve showed high consistency between the observed and predicted results. The decision curve analysis (DCA) revealed that the nomogram was clinically useful. The predictive ability of this nomogram is better than that of albumin level and PG-SGA score.ConclusionThe preoperative nutritional status of GI cancer patients has a significant effect on the occurrence of PPOI. The nomogram developed in this study accurately predicted PPOI in GI surgery patients.